Role of sonic hedgehog signaling pathway in the regulation of ion channels: focus on its association with cardio-cerebrovascular diseases - Ming-Rui Li; Xiu-Ju Luo; Jun Peng (Journal of Physiology and Biochemistry, 2023)

Discrete element-based regression analysis of initial ground stress and application to an extra-long tunnel in China - Ming-Rui Luo; Cheng-You Zhang; Bo Wang; Yan-Hua Zeng (Bulletin of Engineering Geology and the Environment, 2023)

Analysis of spatial and temporal variation of vegetation NPP in Daning River Basin and its driving forces - Wenqian Bai; Li He; Zhengwei He; Xueman Wang; Yang Zhao; Rui Qu; Fang Luo; Xin Chen; Zhifei Wang; Ming Liu (International Journal of Remote Sensing, 2023)

Rapid imaging approach for marine controlled-source electromagnetic with deployed transmission system - Rui Yang; Xuben Wang; Meng Wang; Xianhu Luo; Ming Deng; Jianen Jing; Kai Chen (Journal of Applied Geophysics, 2023)

Phytoplankton control by stocking of filter-feeding fish in a subtropical plateau reservoir, southwest China - Chaoshuo Zhang; Feng Mei; Bin Luo; Dongxu Zhang; Xinyu Cheng; Yongying Xiong; Jianghui Bao; Rui Duan; Hao Jiang; Erik Jeppesen; Ming Duan (Frontiers in Marine Science, 2023)
Stocking of filter-feeding fish (mainly Hypophthalmichthys molitrix and Aristichthys nobilis ) is a common method used in lakes and reservoirs in (sub)tropical China to control phytoplankton, but the results are ambiguous and lack long-term data to support. We analysed a decade (2010-2020) of monitoring data from a subtropical plateau reservoir, southwest China, to which filter-feeding fish were stocked annually. We found that the total phytoplankton biomass, cyanobacteria biomass and average individual mass of phytoplankton decreased significantly during the study period despite absence of nutrient concentration reduction. However, the grazing pressure of zooplankton on phytoplankton also decreased markedly as judged from changes in the ratio of zooplankton biomass to phytoplankton biomass and Daphnia proportion of total zooplankton biomass. This is likely a response to increasing predation on zooplankton by the stocked fish. Our results also indicated that water temperature, total phosphorus and water level promoted phytoplankton growth. Our results revealed that filter-feeding fish contributed to the decline in the biomass of phytoplankton but that it also had a strong negative effect on the grazing pressure of zooplankton on phytoplankton, even in this deep reservoir where zooplankton may have a better chance of survival through vertical migration. The particular strong effect on zooplankton is most likely due to imbalance of stocking and harvesting of fish. In the management of eutrophic reservoirs, the reduction of external nutrient loading should have highest priority. In highland (low temperature) deep-water eutrophic reservoirs, stocking of filter-feeding fish may help to control filamentous phytoplankton provided that the fish stocking is properly managed. The optimal stocking intensity of filter-feeding fish that can help control phytoplankton in such reservoirs without excessive impact on large-bodied zooplankton is a topic for further elucidation, however.

MiR-130/SNAP-25 axis regulate presynaptic alteration in anterior cingulate cortex involved in lead induced attention deficits - Tao Wang; Rui-Li Guan; Yun-Feng Zou; Gang Zheng; Xue-Feng Shen; Zi-Peng Cao; Rui-Hua Yang; Ming-Chao Liu; Ke-Jun Du; Xue-Hang Li; Michael Aschner; Ming-Gao Zhao; et al. (Journal of Hazardous Materials, 2023)

Retraction Note: Cancer-derived exosomal miR-221-3p promotes angiogenesis by targeting THBS2 in cervical squamous cell carcinoma - Xiang-Guang Wu; Chen-Fei Zhou; Yan-Mei Zhang; Rui-Ming Yan; Wen-Fei Wei; Xiao-Jing Chen; Hong-Yan Yi; Luo-Jiao Liang; Liang-sheng Fan; Li Liang; Sha Wu; Wei Wang (Angiogenesis, 2023)